Improving Learning Outcomes of Pythagorean Theorem using STAD Cooperative Learning Type for 8th Grade Students at SMPN 1 Rindingallo - Luther Tandiarrang (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2021)
The objective of this research is to improve the learning outcomes of the Pythagorean Theorem using the STAD Cooperative Learning Type for 8th grade students at SMPN 1 Rindingallo. The research method employed in this study is Action Research, consisting of two cycles, with each cycle comprising Planning, Implementation, Observation, and Reflection. Based on the action research findings, it is concluded that the STAD Cooperative Learning Type can enhance the learning outcomes of the Pythagorean Theorem for 8th grade students at SMPN 1 Rindingallo. Furthermore, the researcher recommends that (1) teachers facing similar difficulties should implement the STAD Cooperative Learning Type to improve learning outcomes, and (2) for optimal results, teachers are encouraged to create more engaging and varied STAD Cooperative Learning activities.